Structure and transformation : theory and society in India - Visvanathan, Susan; Visvanathan, Susan (New Delhi ; New York : Oxford University Press, 2001)
Contributed articles.
Structure and culture : the debates / Sheena Jain -- Framework in change : colonial Indian society / Satish Saberwal -- On understanding caste and class / K.L. Sharma -- Forest dwellers and tribals in India / Savyasaachi -- Anomie, alienation, and involvement / Kuriakose Mamkoottam -- Gender and work in Indian society / Cherian Joseph -- Women and migration / Tulsi Patel -- Interpretations of the city / Susan Visvanathan -- Plantation labour in South and South-East Asia / Shobhita Jain -- Religion and the Geddesian theory of the city / Shiv Visvanathan.
Includes bibliographical references and index.
Keywords: Sociology -- India; India -- Social conditions -- 1947-